2016
DOI: 10.1161/jaha.116.003529
|View full text |Cite
|
Sign up to set email alerts
|

Intima–Media Thickness Is Linearly and Continuously Associated With Systolic Blood Pressure in a Population‐Based Cohort (STANISLAS Cohort Study)

Abstract: BackgroundCarotid intima–media thickness (cIMT) is a noninvasive marker of cardiovascular risk. The cIMT may be increased in patients with harmonisation, but little is known regarding the functional form of the association between blood pressure (BP) and cIMT in hypertensive and nonhypertensive persons. We aimed to define the shape of the association between BP and cIMT.Methods and ResultsWe studied cIMT and ambulatory BP monitoring data from a single‐center, cross‐sectional, population‐based study involving 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 52 publications
5
48
1
5
Order By: Relevance
“…19, 39 Numerous studies have found that the SBP but not DBP was independently associated with IMT, and SBP was more closely related with LVM than DBP. 4045 These findings suggest that at younger age SBP may increase left ventricular afterload with ensuing cardiac structural and functional changes. DBP elevation reflects more an increase of vascular resistance which is a chronic adaptive process leading to vascular remodeling 46, 47 .…”
Section: Discussionmentioning
confidence: 94%
“…19, 39 Numerous studies have found that the SBP but not DBP was independently associated with IMT, and SBP was more closely related with LVM than DBP. 4045 These findings suggest that at younger age SBP may increase left ventricular afterload with ensuing cardiac structural and functional changes. DBP elevation reflects more an increase of vascular resistance which is a chronic adaptive process leading to vascular remodeling 46, 47 .…”
Section: Discussionmentioning
confidence: 94%
“…Both BP and heart rate are correlated with other cardiovascular measures, namely PWV, cIMT and LVMI[35-37]. To assess the causal association between BMI and these cardiovascular measures, independent of BP and heart rate, we took the residuals of the regression between each of these variables and both BP and heart rate and repeated MR and RbG main analyses using these residuals.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…These include measures of arterial stiffness, flow‐mediated dilation (FMD), and carotid intima‐media thickness (cIMT), which all have been shown to be predictive of cardiovascular morbidity and mortality in adulthood . Age, sex, blood pressure, and obesity are well‐described modifiers of these noninvasive measures of subclinical atherosclerosis . From a cardiovascular disease prevention perspective, understanding the multitude of factors and their corresponding level of contribution to adverse subclinical atherosclerotic risk may aid in risk stratification for individuals early in life.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Age, sex, blood pressure, and obesity are well-described modifiers of these noninvasive measures of subclinical atherosclerosis. [10][11][12][13][14] From a cardiovascular disease prevention perspective, understanding the multitude of factors and their corresponding level of contribution to adverse subclinical atherosclerotic risk may aid in risk stratification for individuals early in life.…”
mentioning
confidence: 99%